Eternity in Time—Time in Eternity: Temporality and the Human Self in the Eschaton. (November 2019) - Tóth, Beáta
By interviewing four interlocutors (Karl Rahner, Hans Urs von Balthasar, Joseph Ratzinger, Jean-Luc Marion, and indirectly a fifth, Augustine of Hippo), this article attempts to open up the conceptual and imaginative space in which the issue of the temporality of the human self within the eschaton may be dealt with in a more consistent manner. The strengths and weaknesses of these accounts—which at several points may be seen as complementing one another—reveal the need for a complex treatment reconfiguring theological anthropological thought along the lines of this traditionally less developed and yet intriguing question.